Vitexin attenuates cisplatin-induced renal toxicity by reducing oxidative stress and inflammation - Muhammad Umar Ijaz (Elsevier, 2021)
Cisplatin (CP) is one of the most effective chemotherapeutic drugs used to treat different tumors. Vitexin (VIT) is a natural flavonoid having various pharmacological activities along with its curative effects. The present research was planned to evaluate the therapeutic potential of VIT on cisplatin-induced renal damage in male albino rats. Twenty-four male albino rats were divided into four equal groups. These groups were treated with CP (10 mg/kg injection on the first day of trial) administered group, cotreated (CP; 10 mg/kg + VIT; 10 mg/kg) and only VIT (10 mg/kg orally till the end of the trial) treated group and a control. CP administration significantly decreased the activities of catalase (CAT), superoxide dismutase (SOD), peroxidase (POD), glutathione S-transferase (GST), glutathione (GSH), and glutathione reductase (GSR). The levels of thiobarbituric acid reactive substances (TBARS) and hydrogen peroxide (H2O2) were increased. CP-treatment significantly increased the levels of urea, creatinine, kidney injury molecule-1 (KIM-1), and neutrophil gelatinase-associated lipocalin (NGAL) while considerably reducing the creatinine clearance. The results demonstrated that CP significantly increased the inflammation markers, including tumor necrosis factor-α (TNF-α), nuclear factor kappa B (NF-κB), Interleukin-1β (IL-1β), Interleukin-6 (IL-6) levels and cyclooxygenase-2 (COX-2) activities and histopathological damages. However, co-treatment with VIT efficiently minimized the CP-induced biochemical, inflammatory, and histopathological impairments in rat kidneys. The study's outcomes indicated the significant curative efficacy of VIT to overcome CP-induced nephrotoxicity in male albino rats.